The girl with a mind for math : the story of Raye Montague - Mosca, Julia Finley; Rieley, Daniel (Seattle, WA : The Innovation Press, 2018)
A brief rhyming account of the childhood and work of United States Naval Engineer, Raye Montague who had to deal with prejudices and racial inequality to create the first computer generated rough draft of a U.S. Naval ship and also was the first female program manager of ships in the United States Navy.
School Library Journal, August 2018
Kirkus Starred, August 2018
Booklist, August 2018
3.1
K-3
P
Keywords: Montague, Raye, -- 1935- -- Juvenile literature; Marine engineers -- United States -- Biography -- Juvenile literature; African American engineers -- Biography -- Juvenile literature; Montague, Raye, -- 1935-; Engineers; African Americans -- Biography; Women -- Biography; Biographies